Analysis of the Influence of Workload on Employee Performance Through Work Stress at Police Unit Office Binjai City Civil Service - L. Tobing, Herianto; B, Mesra (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
The aim of this research is to determine and analyze the influence of workload on employee performance both directly and through work stress at the Binjai City Civil Service Police Unit Office. The type of research is associative quantitative. The population in this study was 90 employees with ASN and honorary status at the Binjai City Civil Service Police Unit Office. The sampling technique in this research uses a saturated sample where the entire population is sampled. The data collection technique that was carried out was by distributing questionnaires. Data analysis in this study used the PLS Structural Equation Model with the Smart PLS 3.0 Application Program. The results of this research show that: 1) Workload has a negative and significant effect on employee performance. 2) Workload has a positive and significant effect on work stress. 3) Work stress has a negative and significant effect on employee performance. 4) Workload has a negative and significant effect on employee performance through work stress at the Civil Service Police Unit Office, Binjai City.